2020
DOI: 10.1021/acs.jpcc.0c02907
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effect of Particle Size on the Low Energy Radiation Response of Ceria

Abstract: Understanding the radiation tolerance of ceramics against low energy heavy ions is important for evaluating their stability against alpha recoils, which are a significant source of damage for their application as nuclear fuels and/or waste immobilization matrices. Radiation response of ceramics is significantly affected by the particle size and microstructure in addition to their crystalline structure. With this motivation, three different particle-sized CeO 2 samples were subjected to irradiation by 400 keV K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The phase and crystalline behavior of both irradiated and unirradiated CeO 2 and Gd-doped ceria has already been much studied in previous research papers and it has been observed that up to 5 mol% Gd doping in ceria, there is no major structural change. 12 The lattice parameters and phase structure, reported by Kalita et al 13 for ceria in their paper, are B0.514 for GDC-S and B0.504 for GDC-L, which are more or less the same in the present case. Therefore, motivated by such results, we have presumed that doping of Gd in pure ceria will not cause any major structural or phase change.…”
Section: Paper Pccpsupporting
confidence: 76%
See 2 more Smart Citations
“…The phase and crystalline behavior of both irradiated and unirradiated CeO 2 and Gd-doped ceria has already been much studied in previous research papers and it has been observed that up to 5 mol% Gd doping in ceria, there is no major structural change. 12 The lattice parameters and phase structure, reported by Kalita et al 13 for ceria in their paper, are B0.514 for GDC-S and B0.504 for GDC-L, which are more or less the same in the present case. Therefore, motivated by such results, we have presumed that doping of Gd in pure ceria will not cause any major structural or phase change.…”
Section: Paper Pccpsupporting
confidence: 76%
“…Synthesis of 5 mol% (Gd 0.05 Ce 95 O 1.975 ) Gd-doped ceria nano-powders was carried out through the self-assisted gel-combustion method. 13 To obtain different grain sizes, the prepared nano-powder was divided into two equal parts, pelletized and sintered at two different temperatures: 800 °C for 2 hours and 1300 °C for 30 hours. Hereafter, the samples sintered at 800 °C and 1300 °C will be represented as GDC-S and GDC-L (S = smaller particle size, L = larger particle size), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…downsizing of materials to nano-dimension, has received significant attention and is being considered as an effective strategy in the context of mitigating the radiation damage in materials. It has been observed that the nano-crystalline (NC) state exhibits enhanced radiation damage tolerance, against low energy ions (S n dominant), when compared to its bulk counterparts 5 , 10 – 20 . We have, however, very recently shown that the better radiation tolerance of NC materials is not always true and designing nano-scale materials in order to lower the irradiation induced damage is not advantageous against high energy ions (S e dominant) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric XRD peaks in the irradiated samples denoting the presence of more than one phase has also been observed in low and high energy irradiation of ceria. 35,36 This implies that the passage of radiation through garnets (YAG and Nd-YAG) is creating compositional inhomogeneity within the material as the manifestation of irradiation damage and defect creation, which results in the appearance of more than one garnet phase. The exact nature of these could be determined by electron microscopy and selected area electron diffraction, which are the future scope of this work.…”
Section: (B) and 4(b))mentioning
confidence: 99%